Comparing student and staff perceptions of the "Educational Climate" in Spanish Dental Schools using the Dundee Ready Education Environment Measure. (15th May 2017) - Tomás, I.; Aneiros, A.; Casares‐de‐Cal, M. A.; Quintas, V.; Prada‐López, I.; Balsa‐Castro, C.; Ceballos, L.; Gómez‐Moreno, G.; Llena, C.; López‐Jornet, P.; Machuca, M. C.; Palés, J.
Abstract: Objective: To compare the perceptions of students and teachers of the "Educational Climate" (EC) in Spanish public dental schools. Methods: A group of 1064 students and 354 teachers from six Spanish public dental schools responded to the DREEM questionnaire. This has 50 items grouped into five subscales: perception of learning (Learning); perception of teachers (Teachers); academic self‐perceptions (Academic); perception of the atmosphere in the faculty (Atmosphere); and social self‐perceptions (Social). The DREEM scale provides results for each item, each subscale and the overall EC. Results: The EC scores were 123.2 (61.6%) for the students and 134.1 (67.0%) for the teachers ( P <.001). The scores of the students and teachers for the subscales were, respectively: 27.9 (58.1%) and 30.2 (63.0 %) for Learning ( P <.001); 26.8 (60.9%) and 32.6 (74.1%) for Teachers ( P <.001); 20.7 (64.7%) and 20.5 (64.0%) for Academic ( P =.333); 29.9 (62.3%) and 33.7 (70.3%) for Atmosphere ( P <.001); and 17.9 (64.0%) and 16.9 (60.5%) for Social ( P <.001). The students identified six problematic items (12.0 %) compared to only two (4.0 %) highlighted by the teachers. Conclusion: The students and teachers considered the EC to be "more positive than negative" in Spanish public dental schools; and the different subscales to be "positive and acceptable." The teachers did, however, evaluate the EC, and specifically the learning‐teaching process, more positively than their students, identifying fewer problematic educational aspects. Both groups agreed on the need to: improve support systems for students who suffer from stress and reduce teaching based on "factual learning."